The performance of first generation Of domesticated javaean barb (Systomus orphoides) fry - Dewi Raden Roro Sri Pudji Sinarni; Kusmini Irin Iriana; Radona Deni; Puteri Fera Permata (E3S Web of Conferences, 2021)
The existence of native fish in Indonesian waters, especially in West Java, is under threat due to environmental damage. The domestication of javaean barb (Systomus orphoides) is directed to save the existence of this species and provide economic benefits for the aquaculture community. This study aims were to obtain information about the potential production of larvae and fry of javaean barb that was reared in ex-situ. The parameters observed were fecundity, fertilization rate, hatching rate, the survival rate of larvae, fry growth rate, feed conversion ratio, and fry survival rate. The results showed that javaean barb could be spawned ex-situ through induce breeding techniques. Fecundity was 96 632 ± 24 012 eggs/fish with a fertilization rate of 98.3 ± 1.50% and a hatching rate of 64.5 ± 27.10%. The survival rate of 3 days old larvae was 85.2 ± 7.50%. The growth rate of javaean barb fry was positive allometric. The weight-specific growth rate was 4.9 ± 0.22 % with an FCR of 1.7 ± 0.28 and survival rate of 89.3 ± 4.16%. The success of ex situ javaean barb seedling production opens opportunities for developing this species cultivation in the future.